Adaptive immune‐mediated host resistance to Toxoplasma gondii is governed by the NF‐κB regulator Bcl‐3 in dendritic cells. Issue 7 (12th May 2015) - Tassi, Ilaria; Claudio, Estefania; Wang, Hongshan; Tang, Wanhu; Ha, Hye‐lin; Saret, Sun; Sher, Alan; Jankovic, Dragana; Siebenlist, Ulrich
<x xml:space="preserve">Abstract</x> The atypical IκB family member Bcl‐3 associates with p50/NF‐κB1 or p52/NF‐κB2 homodimers in nuclei, thereby either positively or negatively modulating transcription in a context‐dependent manner. Previously we reported that Bcl‐3 was critical for host resistance to Toxoplasma gondii. Bcl‐3‐deficient mice succumbed within 3–5 weeks after infection, correlating with an apparently impaired Th1‐type adaptive immune response. However in which cell type(s) Bcl‐3 functioned to assure resistance remained unknown. We now show that Bcl‐3 expression in dendritic cells is required to generate a protective Th1‐type immune response and confer resistance to T. gondii. Surprisingly, mice lacking Bcl‐3 in dendritic cells were as susceptible as mice globally deficient for Bcl‐3. Furthermore, early innate defenses were not compromised by the absence of Bcl‐3, as initial production of IL‐12 by dendritic cells and IFN‐γ by NK cells were preserved. However, subsequent production of IFN‐γ by CD4+ and CD8+ T‐cells was compromised when dendritic cells lacked Bcl‐3, and these mice succumbed at a time when T‐cell‐mediated IFN‐γ production was essential for host resistance. These findings demonstrate that Bcl‐3 is required in dendritic cells to prime protective T‐cell‐mediated immunity to T. gondii.